The effects of demand-resource relationship on work-family conflict under Chinese culture: a cross-sectional study - Li, Tianjiao; Helian, Zhiwei; Hu, Ling; Ma, Mengyuan (Frontiers in Psychology, 2024)
Chinese work and life styles are undergoing dramatic changes caused by constantly changing technology and new policies, and the demand-resource dynamic relationship which leads to work-family conflict (WFC) become more and more complicated. However, very little is known about the combined effects of different factors from work and family on WFC. This paper aims to explore (1) the discrepancy between fit and misfit; (2) the discrepancy of the different degrees of fit and (3) the discrepancy of the different degrees of misfit, from two perspectives: work demand-family resource and work resource-family demand. Data were collected from 745 individuals in China and were analyzed by polynomial regression and response surface. The results demonstrate that low work demand-high family resource gets the lowest WFC, and the fit between work demands and family resources impacts the conflict in a U way; high work resource-low family demand gets the lowest WFC, and the fit between work resources and family demands has negative effects on the conflict. This study took factors from both family and work domains into consideration and explored the effect of their interaction on WFC. By examining the dynamic relationship between demands and resources, adjustments can be made in both domains simultaneously, providing more flexible guidance for management practices that reduce WFC.